Oedipus at Thebes : Sophocles' tragic hero and his time - Knox, Bernard, 1914-2010 (Yale University Press, 1998)
Examines the way in which Sophocles' play "Oedipus Tyrannus" and its hero, Oedipus, King of Thebes, were probably received in their own time and place, and relates this to twentieth-century receptions and interpretations, including those of Sigmund Freud